OBI reduction method using optical carrier suppression - Al-Qdah, Malik T.; Abdul Rashid, Hairul Azhar; Tayahi, M. B.; Chuah, Hean Teik; Abdullah, Mohammad Khazani (Wiley Periodicals, 2007)
Optical Beat Interference (OBI) can adversely affect passive optical networks that employs Multiple Optical Carrier Subcarrier Multiplexing (MOC-SCM). The authors propose an OBI reduction method employing carrier suppressed MOC-SCM system. A mathematical model is developed and an experiment is carried out to analyze the performance of the proposed system. The experimental results are in agreement with the mathematical model, which demonstrate an improvement of 27.8 dB in the carrier-to-interference ratio. (C) 2007 Wiley Periodicals, Inc.